Predictive equations for height estimation using knee height of older Bengalees of Purba Medinipur, West Bengal, India - Kuiti, Binoy; Bose, Kaushik (Anthropological Review, 2016)
For nutritional assessment work for older population, it is important to be able to estimate body height based on knee height. The present report describes three equations for height estimation among older Bengalees based on knee height and compares the results with knee height based formulae developed for several other populations. Anthropometric measurements were analyzed from 114 (62 men and 52 women) older subjects aged >= 55 years. The subjects were randomly selected from two blocks (Contai I and Ramnagar I), at coastal area of Purba Medinipur District in West Bengal, India. A population specific formula for height was created based on knee height of the subjects. These estimated formulae from the present study and fourteen other previously reported formulae were also applied to these older population and the mean estimation errors were statistically compared. Analysis indicated that our derived formulae gave accurate estimation of height among the subjects.